2009
DOI: 10.1051/fruits/2009031
|View full text |Cite
|
Sign up to set email alerts
|

Variabilité de quelques caractères biochimiques des fruits deSclerocarya birrea(A. Rich.) Hochst. au Burkina Faso

Abstract: Variability of some biochemical traits of Sclerocarya birrea (A. Rich.) Hochst. fruits in Burkina Faso. Abstract-Introduction. Sclerocarya birrea (A. Rich.) Hochst. subsp. birrea is an indigenous fruit tree very widespread in Burkina Faso. Although very appreciated by the rural populations for its fruit, it remains not domesticated and underutilized. Until now, studies regarding fruit variation and quality have been focused on S. birrea subsp. caffra originating in Southern Africa. Materials and methods. Fruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
1
7
0
1
Order By: Relevance
“…The dendrogram established for all individuals genotyped, divided S. birrea populations in four groups without reference to site or climatic zone. RAPD polymorphisms of S. birrea obtained in the present report suggested that the intra and inter populations variation previously described for morphological and biochemical characteristics (Bationo- Kando et al, 2008Kando et al, , 2009 were probably associated with environmental than genetics factors. Only environmental conditions are likely to cause a gradual degradation of S. birrea populations and its genetic erosion.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…The dendrogram established for all individuals genotyped, divided S. birrea populations in four groups without reference to site or climatic zone. RAPD polymorphisms of S. birrea obtained in the present report suggested that the intra and inter populations variation previously described for morphological and biochemical characteristics (Bationo- Kando et al, 2008Kando et al, , 2009 were probably associated with environmental than genetics factors. Only environmental conditions are likely to cause a gradual degradation of S. birrea populations and its genetic erosion.…”
Section: Resultssupporting
confidence: 71%
“…The characteristics of climate and ecological eleven sites are given in the Table 1. 85 of 138 plants of S. birrea previously studied morphologically and biochemically (Bationo- Kando et al, 2008Kando et al, , 2009 were genetically characterized.…”
Section: Methodsmentioning
confidence: 99%
“…subsp. birrea and caffra ), but information about this was hardly ever indicated in the reviewed papers, apart from Bationo/Kando et al ., who stated that the data were for S. birrea subsp. birrea .…”
Section: Resultsmentioning
confidence: 99%
“…The higher productivity of this fruit species and its presence in the form of plant communities, account for the commercial and industrial exploitation of its fruit. Bationo-Kando et al (2009) showed that the mean sugar content of the fruit pulp was comparable with industrially exploited mangoes in Burkina Faso. Additionally, when compared with the reference seeds such as peanut, shea nut (Leakey, 1999), Sclerocarya birrea kernels had a more lipid content.…”
Section: Discussionmentioning
confidence: 95%
“…However, studies to date, have focused on genetic diversity (Bationo-Kando et al, 2012), morphology (Bationo-Kando et al, 2008), anatomy (Sérémé, 1996;Diallo et al, 2006), or on the physicochemical composition of S. birrea the fruit (Bationo-Kando et al, 2009). On the other hand, data on the production and exploitation of the plant, by rural and urban populations, are still basic or non-existent.…”
Section: Introductionmentioning
confidence: 99%